REVIEW ON HEALTH EFFECTS OF CHROMIUM EXPOSURE: REFLECTION FROM OXIDATIVE STRESS TOWARDS CARCINOGENICITY - DURGAPADA DOLAI,; SATYAJIT TRIPATHY,; SANKAR KUMAR DEY,; SOMENATH ROY, (International Journal of Pharma and Bio Sciences, 2016)
Recently, the main theme of world is urbanization as well as industrialization as a result, there has been a growing concern about increase in toxic metals contamination i.e. chromium that affect the environment, living organisms and human health. Recently, laboratory and clinical reports about the pathogenesis of the toxicity, carcinogenicity and allergenicity of chromium compounds have been reviewed as a basis for consideration of the mechanisms involved for pathogenecity. Chromium compounds have been proofed as a redox cycling environmental carcinogenic agent that provoke apoptosis as the most important mode of cell death. Defects in apoptosis regulatory mechanisms contribute to carcinogenesis induced by Cr (VI). Activation of apoptosis signaling pathways is tightly linked with the generation of reactive oxygen species (ROS). Exposure to Cr [VI] can result in various point mutations in DNA and to chromosomal fragment, and also the oxidative alteration in proteins. In recent report, we have collected the previous reports and overviewed the cytotoxic as well as genotoxic mechanisms of Cr [III] and Cr [VI]. In conclusion, chromium induced cytotoxicity can be attributed to oxidative stress started from glutathione mediated metal reductive activation and continued by mitochondrial/lysosomal toxic interaction.